Meta-Analysis: The Effect of Social Capital on Depression in Elderly - Amanda Widyarahma; Naili Zahroton Mufidah; Agil Rafi’ah Afandi; Bhisma Murti; Aem Ismail (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: According to WHO (2022), 14% of adults >60 years live with depression which accounts for 10.6% of total disability in the elderly. Depression is associated with an increased risk of premature death, with a potential reduction in life expectancy of around 10 years. Studies report that strengthening social capital can be an effective strategy in preventing and managing depression in the elderly. This study aims to analyze the influence of social capital on depression in the elderly. Subjects and Method: This research is a meta-analysis of the PICO model. Population: elderly. Intervention: high social participation, high social cohesion, high reciprocity, high social trust and high social network. Comparison: low social participation, low social cohesion, low reciprocity, low social trust and low social network. Outcome: depression. The data used involves Google Scholar, PubMed, BMC, Elsevier, ScienceDirect, and Springer Link. Inclusion criteria were full-text articles with a cross-sectional study design using multivariate analysis that included OR values and were published from 2014-2023. Data analysis using the Review Manager 5.3 application. Results: The meta-analysis included 17 cross-sectional studies from Korea, Spain, Japan, Taiwan, the Netherlands, China, and Myanmar. The results showed that the incidence of depression decreased with high social participation (aOR= 0.78; 95% CI= 0.61–1.00; p= 0.050), high social cohesion (aOR= 0.84; 95% CI= 0.72 – 0.99; p= 0.030), high reciprocity (aOR= 0.75; 95% CI= 0.63 – 0.90; p= 0.020), and high social trust (aOR= 0.52; 95% CI= 0.41 – 0.66; p<0.001). Social networks reduce the risk of depression but were not statistically significant a(OR= 0.71; CI 95%= 0.31 – 1.59; p= 0.400). Conclusion: Social participation, social cohesion, reciprocity, and social trust have an effect on reducing the risk of depression in the elderly.